Prevalence, Clinical Manifestations, and Biochemical Data of Hypertensive versus Normotensive Symptomatic Patients with COVID-19: A Comparative Study: Running title: Hypertension and COVID-19 - De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2020)
Background: There is a scarcity of data regarding the effect of hypertension on the clinical presentation and outcome of symptomatic patients with COVID-19 infection in comparison with non-hypertensive patients. Aim of the study: To describe the clinical presentation, radiological and hematological data of a cohort of symptomatic COVID-19 positive hypertensive patients (n=50) in comparison with another cohort of normotensive symptomatic COVID-19 positive patients (n=250) diagnosed at the same time and managed in the same health facilities (from Jan 2020 to May 2020). Associated comorbidities were assessed, and the Charlson Comorbidity Index was calculated. The outcomes, including duration of hospitalization, length of ICU stay, duration of mechanical ventilation, and duration of O2 supplementation, were also assessed. Results: The prevalence of hypertension in symptomatic COVID-19 positive patients was 50/300 (16%; the prevalence of hypertension in Qatari adults is 30%). Hypertensive patients had a higher prevalence of DM, CKD, and cardiac dysfunction compared to normotensive patients (p<0.01).They had a higher Charlson Co-morbidity score (2.3±1.8) compared to the normotensive patients (0.4±0.9) (p<0.01). Clinically and radiologically, hypertensive patients had significantly higher percentage of pneumonia, severe pneumonia, and ARDS versus normotensive patients (p<0.01). CBC and differential WBC did not differ between hypertensive and normotensive patients. Hypertensive patients had significantly higher CRP(58.5±84), compared to normotensive patients (28±59) (p<0.01). Furthermore, a longer duration of hospitalization, intensive care unit (ICU) stay, mechanical ventilation and oxygen therapy versus normotensive patients was also observed. CRP was correlated significantly with the duration of stay in the ICU and the duration for oxygen supplementation (r=0.56 and 0.61, respectively; p<0.01). Conclusions: Hypertensive patients with COVID-19 had a higher inflammatory response (higher CRP levels), a significant increase of comorbidities, and a more aggressive course of the disease necessitating a higher rate of ICU admission, longer requirement for hospitalization and oxygen use compared to normotensive patients.